‘Superstitious and Pagan, or Magical and Diabolical’: Saami shamans and their drums according to Johannes Schefferus’ Lapponia - Alves, Victor Hugo Sampaio (Revista AntHropológicas, 2022)
Johannes Schefferus, professor from the University of Uppsala, has been requested during the year of 1671 to write an essay on the Saami, an indigenous people inhabiting the territory belonging to the Swedish Crown. Schefferus came up with an extensive description on the Saami, comprising subjects going from their physicial and emotional characteristics to their religious beliefs and magical practices, approaching their shamanism. Our aim is to highlight the construction Schefferus has made of the image regarding Saami shamanism, the shaman and the use of drums, contrasting such information with what is known today about these aspects. We intend to explicit how the Saami and their identity were perceived by Schefferus as a deviation of ‘european ethos’, since they were still holding into primitive and wild aspects, like shamanism and the use of drums Durante o ano de 1671 foi solicitado a Johannes Schefferus, professor da Universidade de Uppsala, que elaborasse um tratado acerca dos povos sámi, indígenas que habitavam o território pertencente à Coroa Sueca. Baseando-se sobretudo em relatos a ele enviados por missionários que haviam estado em diferentes partes da Lapônia e em obras prévias sobre o tema, Schefferus elaborou uma descrição abrangente sobre os sámi, discutindo desde suas características físicas e emocionais até aspectos sobre suas crenças religiosas e práticas mágicas, dentre elas o xamanismo. Nosso objetivo é destacar a construção da imagem, por parte de Schefferus, em torno do xamanismo sámi, da figura do xamã e da ritualística envolvendo os tambores, contrastando-a com o que se sabe, hoje, sobre estes aspectos. Demonstraremos como os sámi e sua identidade eram percebidos como desviantes de uma ‘euro- peidade’, estando intrinsecamente relacionados a elementos tidos por selvagens e primitivos, como o xamanismo.